Floating ability and drug release evaluation of gastroretentive microparticles system containing metronidazole obtained by spray drying - Laís Nohemann; Marina Penteado de Almeida; Priscileila Colerato Ferrari (Universidade de São Paulo, 2017)
Abstract Gastroretentive floating microparticles were developed and evaluated for the controlled metronidazole delivery for treatment of gastric disease. Floating microparticles, varying in proportions of chitosan and hydroxypropyl methylcellulose or ethylcellulose, were obtained by spray drying. Floating microparticles were characterized by physicochemical and in vitro studies, according to their floating ability and drug delivery. Microparticles presented mean diameter from 1.05 to 2.20 µm. The infrared spectroscopy confirmed the drug encapsulation and showed no chemical linkage between microparticles components. X-ray diffraction showed changes in the drug`s solid state, from crystalline to amorphous, indicating partial drug encapsulation, due to the presence of some crystalline peaks of metronidazole in microparticles. All microparticles floated immediately in contact of simulated gastric fluid and both floating and drug release profiles were dependent of microparticles composition. Microparticles samples constituted by chitosan and hydroxypropyl methylcellulose revealed the best relationship between floating duration and drug release, remaining floating during the occurrence of the drug release, ideal condition for the floating gastroretentive systems.